Grammar Teaching and Learning in English Language Class: Students’ View - Normawati, Afi; Nugrahaeni, Dwitiya Ari (English Education:Journal of English Teaching and Research, 2024)
Grammar, which differs in structure among languages, plays an important component of language acquisition. Grammar proficiency is essential for clear communication since it improves understanding and coherence. Therefore, mastering English grammar is essential to EFL study. This study explores the students’ view on the importance of grammar in language acquisition in detail and explores how EFL students evaluate the teaching and learning of grammar. A qualitative method was used, including open-ended questionnaire and interview, to better understand students' perspectives. The results support the participants' understanding of grammar's significance and reinforce the idea that grammar teaching is essential. The findings of this study further highlight the need of combining explicit and implicit teaching strategies within grammar teaching and learning, acknowledging the mutually beneficial nature of both methods. These strategies further emphasise the critical role that technology and the internet play in language learning. These results together offer educators knowledge for developing effective grammar teaching strategies that correspond with students' viewpoints and academic objectives.